Treatment of depression through food and phytotherapy (Research, Society and Development, 2022)
In recent years, the use of herbal medicines and food has shown positive results in the treatment of depression, the objective of this study was to evaluate the effects of the use of omega 3, turmeric and tryptophan in the depression treatment. In the initial research, according to the chosen theme, 4,847 articles were selected by the integrative review of scientific literature, according to consultations and the SCIELO, SCIENCE database DIRECT, WILEY and PubMeD, and at the end, 10 articles were chosen to be used and compose the research. The content was approached in the following way, firstly about the stages of depression and their respective approaches, for deepening, and then the influence of nutrients and physiotherapists in depression, including omega 3, saffron and tryptophan. It is concluded that the adequate consumption of seafood and the choice of natural seasonings, has positive results both in improvement of the symptom, as to avoid the disorder.